Crater production by energetic nanoparticle impact on Au nanofoams - Anders, Christian (2016)
Impact of energetic nanoparticles on solids produces craters on the surface. We use molecular dynamics simulations to compare crater production on a compact Au solid with that in a porous (foam) target. Our results show a complex picture: (i) At low impact velocities, the nanoparticles produce permanent craters in the foam while they cannot penetrate the compact target. (ii) With increasing velocity and/or projectile mass, the crater depth in the foam target increases less strongly than for the compact target. The plasticity-affected zone in the foam target is of similar size as in the compact target. Our results are relevant for the use of porous structures as shields against nanoparticle impact.